(untitled) (Global Journal of Management and Business Research, 2017)
The profitability is the basic objective of all the institutions, and it is necessary for its survival, continuity which achieved this goal through two important decisions: the investment decision, and the decision of funding, therefore it is expected that moving the facility characterized by high profitability rate, the opportunity to capture profits rely on a lesser extent on borrowed money, but a greater degree of ownership and retained earnings.